Modified Transconjunctival Approach to the Lower Eyelid: Technical Details for Predictable Results. Issue 1 (March 2016) - Bonawitz, Steven; Crawley, William; Shores, Jaimie T.; Manson, Paul N.
The transconjunctival approach to the lower orbit is well described in the literature and has been used for both cosmetic and reconstructive purposes. When properly performed, it allows access to the orbital floor and inferior orbital rim with minimal lower lid morbidity and an inconspicuous scar. Many variations of this approach have been described and these can lead to confusion and uncertainty regarding the surgical technique including when and how to best utilize this approach in the traumatized eyelid. Residents and less experienced attendings employing this approach often fail to fully understand the technical and anatomic details that can make this a very fast and simple way to gain complete access to the inferior, medial, and lateral orbit while minimizing complications such as postoperative lid malposition and canthal deformities. We describe our method for transconjunctival access to the inferior orbital rim and orbital floor with specific attention to several precise surgical aspects that make this a fast and reliable technique with low morbidity and predictable architecture of closure.